(untitled) (Journal of Economic Research & Business Administration, 2016)
The article examines trends in the market of consulting services, as well as the use of topical marketing tools in promoting services kazhastanskom market. The features of the consulting services market in particular is determined that the scope of consulting services are characterized by a large range and a high degree of service differentiation. It is noted that the main task of a consulting firm in the field of marketing is to ensure that such communications with the target groups of consumers that will demonstrate the level of competence of key personnel of the company. Particular attention is paid to such instrument of marketing communications as advertising, its specificity and characteristics. With regard to the market of consulting services specified theoretical aspects of goals, means, form, content and frequency of advertising. The conclusions that the specific characteristics of promotional activities on the consulting market improves advertising exposure to the consumer and contribute to the rapid development of business.